Jakarta sejarah 400 tahun / Susan Blackburn; Penerjemah, Gatot Triwira; Penyunting, Retna Kurnia - BLACKBURN, Susan; GATOT Triwira; RETNA Kurnia (Komunitas Bambu, 2012)
xxiv, 391 hlm. : Ilus. ; 24 cm.